Pengaruh Earning Per Share Dan Price Earning Ratio Terhadap Return On Equity Pada Perusahaan Yang Bergerak Di Sektor Pertambangan - Munawar, Aang; Soelehan, Aan (STIE Kesatuan, 2010)
Capital Market is one place for investors to invest capital in the hope of obtaining compensation in the form of return on investment. Investment shares are highly vulnerable to political and economic situation, the stock market will react when problems occur in the country. The financial statements of companies are expected to member information to potential investors and prospective creditors to take decisions related to their fund investments. One of the tools to analyza the return on the capital stock itself is the analysis of financial ratios such as EPS (Earning Per Share) and PER (Price Earning Ratio). The problems studied in this research is How MuchEPS and PER effect on Return On Equity jointly and individually. The purpose of this study was to identify relationships between variables, independent variables affect the dependent variable, and finally to measure how strong the influence of variable X to variable Y. The analytical method used is the Linear Regression. Case study taken at PT Aneka Tambang Tbk, PT TimahTbk, PT Tambang Batubara Bukit AsamTbk, PT Indonesian Natural Resources Tbk, and PT Bumi Resources Tbk. Concluded that overall the Price Earning Ratio influence significantly the level of ROE companies, although on Earning Per Share has no significant effect. Viewed from the five companies it can be concluded that there was no significant on the EPS level of Return On Equity Company.